Associated crimes and responsibilities of entities: thoughts on the sidelines of research (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
Bocconi University’s research analyzed the criminal proceedings started with respect to the crime of mafia-type association in Milan from 2000 to 2015. It also monitored the functioning of the intersection between this crime, as per sec. 416-bis of the Criminal Code, and corporate criminal liability, and found out that Milan’s Court has been making a very limited use of sec. 24-ter of law decree 231/2001 so far. After some remarks on the confiscation of profits deriving from the crimes of criminal association, the paper highlights that from a legal standpoint these crimes are hardly compatible with the concept of “interest/advantage” requested by law decree 231/2001 in order to establish the entity’s liability, and from a factual point of view that it’s difficult to assess the effects of mafia’s penetration into companies, since the entities involved often look favored and strangled at the same time.Key words: mafia-type association; ‘ndrangheta; infiltration; confiscation; law decree 231/2001